Scat detection dogs, DNA and species distribution modelling reveal a diminutive geographical range for the Vulnerable small red brocket deer Mazama bororo. Issue 4 (11th October 2016) - Duarte, José Maurício Barbanti; Talarico, Ângela Cristina; Vogliotti, Alexandre; Garcia, José Eduardo; Oliveira, Márcio Leite; Maldonado, Jesús E.; González, Susana
Abstract: The small red brocket deer Mazama bororo is endemic to the Brazilian Atlantic Forest, a biome that has been greatly fragmented and altered by human activities. This elusive species is morphologically similar to the red brocket deer Mazama americana and the Brazilian dwarf brocket deer Mazama nana, and genetic typing is necessary for reliable identification. To determine the geographical range of M. bororo more accurately, we conducted non-invasive genetic sampling using scat detection dogs trained to locate deer faeces. We surveyed 46 protected areas located within the species' potential distribution and collected a total of 555 scat samples in 30 of the protected areas. Using a polymerase chain reaction–restriction fragment length polymorphism approach, we genotyped 497 scat samples (89%) and detected M. bororo in seven localities in three Brazilian states. The results support a range extension of the small red brocket deer to latitudes 23 and 28°S and longitudes 47 and 49°W. We show that the species' distribution is associated with 37, 517 km 2 of the Ombrophilous Dense Forest in the Brazilian Atlantic Forest, and this conclusion is supported by species distribution modelling. The small red brocket deer is the largest endemic species in Brazil and may have the smallest geographical distribution of any Neotropical deer species. This species occupies fragmented landscapes and is threatened by human encroachment, poaching, and predation by dogs, and based on our findings we recommend policy intervention for conservation planning of the Ombrophilous Dense Forest.